PEMBUATAN DAN PEMANFAATAN SILIKA DARI PASIR PANTAI SEBAGAI BAHAN PEMUCAT UNTUK MENURUNKAN KADAR ASAM LEMAK BEBAS PADA CPO (CRUDE PALM OIL) - Nirwana Nirwana; Alimuddin Alimuddin; Erwin Erwin (PROSIDING SEMINAR KIMIA, 2018)
A study on the manufacture and utilization of silica from coastal sand as a pale ingredient to lower free fatty acid levels has been conducted. The present invention includes sample preparation, sodium silicate (Na2SiO3), silica gel formation, silica gelation and Crude Palm Oil (CPO) test result of bleaching. The results showed that the silica of coastal sand was potential as a crude palm oil (CPO) ingredient with the ability to decrease the free fatty acid and color brightness, on the addition of 1 gram of silica obtained result of free fatty acid content analysis is 24,35 % with decreased color brightness of 0,27% and on the addition of 2 gram of silica obtained result of free fatty acid content analysis is 42,49 % with decreased color brightness of 2,8%. Keywords: Sand Beach Sebatik Island, Silica, Bleaching, Crude Palm Oil (CPO), Free Fatty Acid Levels.